Antioxidant Activity and Lethal 50 Doses of Polyhydroxybutyrate Nanoparticles (PHB-NPs) - Jenan A. Ghafil; May Talib Flayyih (World Journal of Experimental Biosciences, 2022)
Preparing Polyhydroxybutyrate nanoparticles (PHB-NPs) in a safe, economical, and effective manner is one of the biggest challenges facing nanotechnology workers. The current study aims to find an effective and safe way to prepare PHB-NPs. Moreover, to find the antioxidant effect and lethal dose fifty (LD50) of prepared PHB-NPs. The PHB-NPs were prepared by exposing an emulsion of PHB (dissolve 0.5 mg of PHB in 25 ml of deionized distilled water) to ultrasound (4500 kh) for 25 seconds at pH 4, then the pH was elevated to 10 for 18 and after that reduced to 7.1. Anti-oxidant activity was measured by using using 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) radical scavenging assay. The results were compared with ascorbic acid. Lethal dose 50 was measured to prepare PHB-NPs by using the linear assay.  The results proved that the method used in the current study is an effective method in producing the PHB-NPs after testing it under the scanning electronic microscope (SAM), which showed that the obtained particles were nanoparticles (20-22 nm). The results showed the scavenger activity of PHB and PHB-NPs as compared with the scavenger activity of ascorbic acid. Moreover, the scavenger activity of PHB-NPs was higher than the Scavenger activity of PHB (200 and 100 µg/ml). The present study showed that 1500 mg/kg (PHB-NP/animal weight) killed 50 % of laboratory animals, and this percentage is very high, which confirms that PHB-NPs are a safe material. It can be concluded that the affectivity of the studied method in preparing PHB-NPs and these particles have antioxidant activity and are almost safe in vivo.
Keywords: Antioxidant, LD50, Nanoparticles, Polyhydroxybutyrate.